Tih spomin vsem žrtvam boja Diferenciacija in interference v slovenskem pesnjenju med drugo svetovno vojno 1941-1945 - Stanonik, Marija (Poezija konteksta, 2016)
The monograph Iz kaosa kozmos (From Chaos to Cosmos) and the first two books from the Poezija konteksta (Poetry of Context) series explore the poetry created during the period of the Slovenian resistance movement and the related revolution during the Second World War (1941-1945). The third and fourth book analyze the poetry created by Slovenians who in the Second World War were forcefully drafted into the German army~Slovenians who lived in the period of the Italian occupation of the Slovenian territory under the 1920 Treaty of Rapallo~and those who were mobilized into the Italian army during WWII.